Multiple Beam Laser Guidance for Patterning Irregularly Shaped Cells - Schmidt, Lucas; Wang, Zhonghai; Yang, Xiaoqi; Ye, Tong; Borg, Thomas K.; Shao, Yonghong; Gao, Bruce Z. (Frontiers in Physics, 2020)
Laser cell patterning is a distinctly effective technique for creating cell arrangements in a culture that replicates in vivo tissue structure for studying contact-mediated cell-cell interactions. Conventional laser-based single-cell-manipulation techniques are limited by their inability to pattern irregularly shaped cells, such as rod-shaped cardiomyocytes. We report the use of a spatial light modulator loaded with a computer-generated phase map to shape a single laser source into multiple laser-guidance beams distributed around the outer contour of an irregularly shaped cell to achieve accurate cell patterning. In addition to describing the principle and practice of the system design, we present what is to our knowledge the first achievement of patterning large, irregularly (rod) shaped adult rat cardiomyocytes in an end-to-end connected alignment to replicate the in vivo heart muscle cell connection without the use of substrate surface modifications, which can interfere with in vivo-like cell-cell and cell-extracellular matrix interactions. Our research demonstrates that two-stage multiple-beam laser guidance is effective: 1) A dual-beam configuration horizontally translates a cell from the outlet of the microfluidic cell delivery channel to a position above the cell deposition site and 2) A quad-beam configuration rapidly propels the cell axially through the suspension medium to the culture substrate with the vertical movement of the cell patterning chamber. Our study reveals that 90% of the patterned cells maintained end-to-end connection 30 minutes after patterning, and mechanical junctions could be reinstalled between laser connected cells after overnight incubation. This demonstrates that multiple-beam laser patterning is an outstanding tool for in vitro studying contact-mediated cell-cell interactions among irregularly shaped cells.